Horizontal Urban Expansion And Livelihood Adjustment Problem Among Ex-Farmers In The Kebeles Surrounding Jimma Town: The Case Of Derba Kebele - Tamirat Mengistu (European Scientific Journal, ESJ, 2016)
This study is aimed at examining the livelihood strategy, benefit packages offered, adjustment problems and the coping strategies of exfarmers in the re-located neighbourhood of Derba kebele in Jimma town. To this end, the research site was purposively selected and in-depth interview with key informants; one focus group discussions and observation were used to collect the data required for the study. The study result showed that the livelihood of ex-peri-urban community has been jeopardized following the relocation to Hirmata Mercato kebele. This is because of the changes in the contexts that surrounds rural area and urban area. Since urban contexts are distinct from the rural ones and the households were not ready to be familiarized with the situation,and also the nature of follow-up and support given at post displacement time was less, majority of them lead a precarious living condition. As a result, majority of the households are not contented with the livelihood they are leading in the Hirmata Mercato Kebele.